Self-referential belief shares common neural correlates with general belief - Bruns, Emily; Scholz, Immanuel; Koppe, Georgia; Kirsch, Peter; Gerchen, Martin Fungisai (Scientific reports, 2025)
Belief processing and self-referential processing have been consistently associated with cortical midline structures, and cortical regions such as the vmPFC have been implicated in general belief processing. The neural correlates of self-referential belief are yet to be investigated. In this fMRI study, we presented 120 statements with trait adjectives to N = 27 healthy participants, who subsequently judged whether they believed these trait adjectives applied to themselves, a close person, or a public person. Thereafter, participants rated their certainty in this judgment. Expectedly, self-referential processing evoked a large cluster in the vmPFC, ACC, and dmPFC. For belief, we found a cluster in the vmPFC, ACC, and amPFC during statement presentation, partially overlapping with that for self-referential processing. The cluster for self-belief vs. disbelief was similar in location and size to that for general belief processing. For uncertainty, we found dmPFC activation. We replicated vmPFC involvement in belief processing and found a common neural correlate for belief and self-belief in the vmPFC. Furthermore, we replicated the role of the dmPFC in uncertainty, supporting a dual neural process model of belief and certainty.